The Effects of Maternal Intake of EPA and DHA Enriched Diet During Pregnancy and Lactation on Offspring’s Muscle Development and Energy Homeostasis - Ghnaimawi, Saeed; Zhang, Shilei; Baum, Jamie I.; Huang, Yan (Frontiers in Physiology, 2022)
EPA and DHA are n-3 long-chain polyunsaturated fatty acids with a diversity of health benefits on offspring. The objective of this study was to test the in vivo effect of maternal ingestion of EPA and DHA on fetal and offspring muscle development and energy balance. Two groups of female C57BL/6 mice were fed EPA and DHA enriched diet (FA) and diet devoid of EPA and DHA (CON) respectively throughout the entire period of gestation and lactation. Embryos at E13 and offspring at age of D1 and D21 were selected for sample collection and processing. No change in birth number and body weight were observed between groups at D1 and D21. Transient increase in the expression levels of myogenesis regulating genes was detected at D1 (P<0.05) in FA group. Most of the expression of muscle protein synthesis regulating genes were comparable (P>0.05) between FA and CON groups at D1 and D21. The significant increase in MHC4, and IGF-1 was not linked to increased muscle mass. A persistent increase in ISR expression (P<0.05) but not in GLUT-4 (P>0.05) was detected in offspring. Up-regulation of adipogenesis regulating genes was accompanied by increasing intramuscular fat accumulation in the offspring of FA group. Considerable increase in transcripts of genes regulating lipid catabolism and thermogenesis in liver (P<0.05) was noticed in FA group at D21; whereas, only the levels of Cpt1α and Ehhadh increased at D1. Similarly, genes regulating lipolysis were highly expressed at D21 in FA group. EPA and DHA treatment promoted BAT development and activity by increasing the expression of BAT signature genes (P<0.05). Also, maternal intake of EPA and DHA enriched diet enhanced browning of sWAT. Taken together, maternal ingestion of EPA/DHA may be suggested as a therapeutic option to encounter childhood obesity and confer long-lasting metabolic benefits on offspring.